2019
DOI: 10.1111/bdi.12856
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal perfusion fluctuation and perfusion connectivity in bipolar disorder measured by dynamic arterial spin labeling

Abstract: Objectives:We sought to evaluate whether dynamic Arterial Spin Labeling (dASL), a novel quantitative technique robust to artifacts and noise that especially arise in inferior brain regions, could characterize neural substrates of BD pathology and symptoms.Methods: Forty-five subjects (19 BD patients, 26 controls) were imaged using a dASL sequence. Maps of average perfusion, perfusion fluctuation, and perfusion connectivity with anterior cingulate cortex (ACC) were derived. Patient symptoms were quantified alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Early on, it was shown that connectivity of the sensorimotor network could be detected with ASL by evaluating fluctuations in the CBF signal. 139 Since then, several studies performed to identify resting state networks, applying different analysis methods, such as seed-based connectivity, [140][141][142] independent component analysis [143][144][145][146][147] and whole-brain voxel level connectivity, 143,148 have found similar brain networks as those observed in resting state BOLD studies. As in the case of task activation studies, resting-state functional connectivity measured with ASL can potentially provide better localization of resting state networks than BOLD, despite the lower spatial resolution of the ASL images.…”
Section: Asl Functional Mri (Fmri)mentioning
confidence: 99%
“…Early on, it was shown that connectivity of the sensorimotor network could be detected with ASL by evaluating fluctuations in the CBF signal. 139 Since then, several studies performed to identify resting state networks, applying different analysis methods, such as seed-based connectivity, [140][141][142] independent component analysis [143][144][145][146][147] and whole-brain voxel level connectivity, 143,148 have found similar brain networks as those observed in resting state BOLD studies. As in the case of task activation studies, resting-state functional connectivity measured with ASL can potentially provide better localization of resting state networks than BOLD, despite the lower spatial resolution of the ASL images.…”
Section: Asl Functional Mri (Fmri)mentioning
confidence: 99%
“…This would enable study of the blood flow modulations at rest, potentially both from vasoregulatory changes and from correlated neural activity. In some pathologies, fluctuations may be more diagnostic than mean blood flow values ( Dai et al, 2020 ). Of course, modulations of blood flow may also be stimulated for diagnostic and research purposes, such as by CO 2 ( Last et al, 2007 ) or acetazolamide ( Detre et al, 1999 ; Dai et al, 2020 ), blood pressure cuffs ( Panerai et al, 2001 ), respiratory protocols ( Detre et al, 1999 ; Puig et al, 2019 ), and electrical ( Zheng et al, 2011 ) or task based ( Kim, 1995 ) brain activity stimulations.…”
Section: Discussionmentioning
confidence: 99%
“…MRI data were acquired on 3T scanners: GE Signa HDxt (Boston) and Philips Achieva (Dallas). The GE scanner pCASL sequence 24 used a 3D stack of spiral RARE readout with a labeling duration (LD)=2000msec, post‐labeling decay (PLD)=1800msec, background suppression to less than 0.3% of background tissue signals and scan time (ST)=9:00min 24‐26 . The reference volume was collected for the purpose of CBF quantification.…”
Section: Methodsmentioning
confidence: 99%
“…CBF‐weighted images were corrected for head motion and a mean head‐motion corrected image was generated. No subjects were dropped due to motion 26,27 . The GE CBF map for each subject was quantified using the standard kinetic model 28‐30 along with the mean of the head‐motion corrected ASL images and the reference image.…”
Section: Methodsmentioning
confidence: 99%